Pendampingan Baca Tulis Qur’an Bagi Anak Anak KKN Desa Sasak Panjang RT 002 RW 003 - Nurul Hamidah; Sabina Alfani; Fadlatul Musyarofah; Lulu Baldah Toyibah; Rahmat Ado Lewar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
After conducting a survey to the community, it was found that there are still many children who cannot read the Qur'an in accordance with tajwidmya. Meanwhile, the age of children is the right time to learn. The number of children who are still not fluent and still not in accordance with all the laws of reading the Qur'an, so the assistance in learning the Qur'an with the application of the iqra' method at TPQ Musholah Nurul Iman Sasak Panjang Village RT 002 RW 003 Tajur Halang Village, Bogor Regency which is carried out by IAI National Thematic KKN students Laa Roiba Bogor as a form of community service, aims to make children love the Qur'an more, increase interest and diligence in learning the Qur'an, know the correct reading law in accordance with the rules of reading law, makhrajul letters, tajwid, and so on. The method used in this community service is the ABCD (Asset Based Community- driven Development) method. The results of the service show that children who used to not know the rules of the law of reading, the words and tajweed in reading the Qur'an, after the implementation of the Thematic KKN student service in the community in this assistance makes the children know more and can practice the legal rules of the correct reading of the Qur'an. The coaching program is carried out through assistance in eradicating Al Quran illiteracy through the Iqra method. Initial observation through interviews with religious leaders and several communities. This activity is divided into three classical, namely; Opening activities (Early classical), Core activities and Closing activities (Late classical).